2021
DOI: 10.1080/17453674.2021.1876996
|View full text |Cite
|
Sign up to set email alerts
|

Good clinical outcome for the majority of younger patients with hip fractures: a Swedish nationwide study on 905 patients younger than 50 years of age

Abstract: Hedström (2021): Good clinical outcome for the majority of younger patients with hip fractures: a Swedish nationwide study on 905 patients younger than 50 years of age, Acta Orthopaedica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…One could argue that there are few very young patients in our cohort, 91% of the patients are aged 40 to 59 years, but this is coherent with a Danish register study where 90% of hip fractures in patients under 65 years of age are found in patients aged 40 to 65 [4]. In a Swedish register study on patients with hip fractures younger than 50 years, the median age was 42 [47]. When excluding patients aged 50-59, our cohort show a corresponding median age of 44; hence, we consider our sample sufficiently representative.…”
Section: Limitationssupporting
confidence: 85%
“…One could argue that there are few very young patients in our cohort, 91% of the patients are aged 40 to 59 years, but this is coherent with a Danish register study where 90% of hip fractures in patients under 65 years of age are found in patients aged 40 to 65 [4]. In a Swedish register study on patients with hip fractures younger than 50 years, the median age was 42 [47]. When excluding patients aged 50-59, our cohort show a corresponding median age of 44; hence, we consider our sample sufficiently representative.…”
Section: Limitationssupporting
confidence: 85%
“…Other studies have showed that among all patients with hip fractures, approximately 2-11% of them are younger than 50 years old [34]. The latest research shows that the proportion of patients with hip fractures under the age of 50 with femoral neck fractures is 58% [35].…”
Section: Discussionmentioning
confidence: 98%
“…The database consisted of 1465 patients over 60 years of age that had suffered a hip fracture. Patients below the age of 60 years were excluded as mortality rates in younger patients that suffer hip fractures are drastically lower and we wanted to focus on potentially frail patients with health issues related to aging [ 20 , 21 ]. Patients with ASA 5 or 6 ( n = 1) were excluded.…”
Section: Methodsmentioning
confidence: 99%